Subcutaneous Implantation of Hepatocellular Carcinoma in a Dog. (November 2022) - Peterson, Marisa R.; Porter, Brian F.; Edwards, Erin E.; Piccione, Julie
Summary: A 13-year-old male neutered Cocker Spaniel mixed-breed dog developed a subcutaneous mass 2 years after undergoing surgery to remove a hepatocellular carcinoma. An approximately 4 × 3 cm subcutaneous mass was found on the ventral abdomen at the cranial end of the abdominal incision from the previous surgery. The subcutaneous mass was surgically removed and histopathological examination determined that it was an implantation of the previously excised hepatocellular carcinoma. The diagnosis was confirmed by immunohistochemical labelling with hepatocyte paraffin 1 antibody and pancytokeratin. Based on the location of the subcutaneous mass at the cranial end of the abdominal incision associated with the previous hepatocellular carcinoma resection, it is likely there was iatrogenic metastasis from the primary tumour excision. Subcutaneous iatrogenic metastasis of hepatocellular carcinoma is well recognized in humans but has apparently never been reported in dogs. Clinicians should be aware of this potential surgical complication.